THE LEVEL OF ORGANIZATIONAL LOYALTY IN ECONOMIC INSTITUTIONS: A CASE STUDY OF HOLCIM CEMENT COMPANY IN M’SILA - Salem Slimane (International Journal of Innovative Technologies in Social Science, 2024)
This research investigates the degree of organizational loyalty exhibited by employees at Lafarge Holcim Cement Company, located in Hammam Dalaa, M’sila. It further examines the potential correlation between this loyalty and key demographic variables, including gender, age, educational attainment, and length of service within the organization. Employing a descriptive-analytical methodology, the study was designed to answer its central research question concerning the extent of employee loyalty at the specified company. A comprehensive theoretical framework was established, and a tailored questionnaire was developed as the primary instrument for measuring organizational loyalty. The research was conducted among a population of 450 employees, from which a sample of 40 individuals was selected for in-depth analysis. The results demonstrated a notably high overall level of organizational loyalty among the workforce. Statistical analysis revealed that loyalty levels did not vary significantly across different categories of gender, age, or educational background. However, a statistically significant relationship was identified between organizational loyalty and the duration of an employee’s experience within the company, indicating that length of service is a influential factor.